Study on the formation of current characteristics of a silicon photodiode with rectifying barriers - Karimov, A. V.; Yodgorova, D. M.; Giyasova, F. A.; Mirdzhalilova, M. A.; Asanova, G. O.; Abdulkhaev, O. A.; Mukhutdinov, Zh. F. (Technology and design in electronic equipment, 2013)
The article presents the results of studies on silicon photodiode double-barrier structure with back-to-back rectifying junctions «metal — semiconductor» in the photodiode and photovoltaic modes. Such structures are of interest for the development of input devices for weak optical signals.